Upper extremity muscle activation during drive volley and groundstroke for two-handed backhand of female tennis players - Tai, M.-L.; Yang, C.-J.; Tang, W.-T.; Elliott, B.; Chang, K.-L. (Journal of Sports Science & Medicine, 2022)
Drive volley is one of the essential backhand stroke technique trends seen in recent women`s tennis competitions. Although movements of the drive volley and groundstroke are similar, activation of the internal muscles vary due to different incoming ball conditions. Most previous studies only focused on the groundstroke, however. The current study investigates the different muscle activation patterns in the upper extremity muscle during the two-handed backhand drive volley as well as the groundstroke for female tennis players. Ten elite female tennis players were measured in the muscle activation of the flexor carpi radialis (FCR), extensor carpi radialis (ECR), biceps brachii (BB), and triceps brachii (TB) from both upper extremities. Racket-head speed at impact, swing duration of each phase, and racket-head average velocity in both strokes were also recorded. Significant differences were found between the drive volley and groundstroke in the velocity profile of racket tip, swing duration of each phase (preparation, early follow-through, and late follow-through), activation patterns of upper extremity muscles, and flexor/ extensor ratios of wrist and elbow in both upper extremities. Different racket trajectory strategies were also observed between the two strokes, with greater horizontal racket velocity recorded in the groundstroke but greater vertical velocity in the drive volley. ECR and TB muscle activation during the drive volley preparation phase was greater than the groundstroke when completing a quicker backswing. In the early acceleration phase, the greater FCR leading arm activation in the drive volley assisted wrist stabilization in preparation for impact. In the late follow-through phase, less TB leading arm activity and higher ECR trailing arm activity in the drive volley showed more forward compression movement in racket contact with the ball. As it is essential for the drive volley to complete a quicker backswing and to increase shot efficiency at the end of the forward movement, coaches should consider the two strokes` muscle activation and technique differences to enhance specific techniques and fitness training programs.